Improved OFF-state breakdown voltage in AlGaN/GaN HEMTs grown on 150-mm diameter silicon-on-insulator (SOI) substrate - Dolmanan, S. B. (2013)
The AlGaN/GaN-based high-electron-mobility transistors (HEMTs) are suitable for discrete components in many high power and high frequency power electronics applications useful for communications, satellites, power amplifiers, inverters/converters for electric and/or hybrid vehicles. Presently, these devices are commonly grown on sapphire, silicon carbide, and recently on 100- to 200-mm diameter silicon substrates. For a large scale deployment of low cost GaN-based power electronic devices, silicon substrate offers tremendous opportunities due to mature back-end Si process technologies. However, GaN epilayers on large area Si substrates results in severe wafer bowing and cracking due to high thermal mismatch between nitride layer and the substrate. As an alternative to Si substrate, silicon-on-insulator (SOI) substrate has been used for the demonstration of GaN-based light emitting diodes (LEDs)[1]. To the best of our knowledge, the demonstration of AlGaN/GaN transistors on a thin SOI substrate is rather limited. In this study, we report on the growth and characteristics of AlGaN/GaN heterostructures (HSs) on 150-mm diameter Si(111) and SOI(111) substrates. In addition, fabrication of HEMTs and device characteristics will be discussed on the SOI platfrom.